2022
DOI: 10.1136/bmjgh-2022-009849
|View full text |Cite
|
Sign up to set email alerts
|

Cancer research across Africa: a comparative bibliometric analysis

Abstract: IntroductionResearch is a critical pillar in national cancer control planning. However, there is a dearth of evidence for countries to implement affordable strategies. The WHO and various Commissions have recommended developing stakeholder-based needs assessments based on objective data to generate evidence to inform national and regional prioritisation of cancer research needs and goals.MethodologyBibliometric algorithms (macros) were developed and validated to assess cancer research outputs of all 54 African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…A recent bibliometric analysis of cancer research across Africa showed that SSA contributes only 22% (5281/23 679 papers), of which 42% is from South Africa. 16 Together, South Africa and Egypt contribute 62% of cancer research papers from Africa. 16 As most research from Africa is a result of north–south collaboration, researchers from HICs tend to prioritise collaborations with countries and hospitals where there is a large patient population or where they have previously conducted research.…”
Section: Where In Africa Is Cancer Research Done?mentioning
confidence: 99%
See 3 more Smart Citations
“…A recent bibliometric analysis of cancer research across Africa showed that SSA contributes only 22% (5281/23 679 papers), of which 42% is from South Africa. 16 Together, South Africa and Egypt contribute 62% of cancer research papers from Africa. 16 As most research from Africa is a result of north–south collaboration, researchers from HICs tend to prioritise collaborations with countries and hospitals where there is a large patient population or where they have previously conducted research.…”
Section: Where In Africa Is Cancer Research Done?mentioning
confidence: 99%
“… 15 This was further confirmed by a comparative bibliometric analysis of cancer research across Africa over a 12-year period (2009–2020), which found that for a total of 5303 papers from SSA, African researchers were likely to be the first author in only 42% and the last author in 30%. 16 As evidenced by these two reviews, the lack of research leadership among African researchers spans all research types from clinical trials to observational studies—majority of the studies in these reports are observational. Additionally, there is clear evidence of major imbalances in global cancer research priorities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several fields covered by these three clusters are still incubating and do not explain the huge gaps between North Africa and Sub-Saharan Africa such as Nanomedicine [120], clinical decision support [121,122] and Drug Discovery [123]. The publication bias towards North Africa is mainly explained by the higher research productivity of this region in fields like Oncology [124], Radiology [125], and Biochemistry [126].…”
mentioning
confidence: 99%